Storm surge and hurricane safety with North Atlantic tracking chart. - United States. National Weather Service ([Silver Spring, Md.] : Dept. of Commerce, National Oceanic and Atmospheric Administration, [Office of Oceanic and Atmospheric Services], National Weather Service, 1979)
Mode of access: Internet.